Pandangan Islam terhadap Islamophobia - Fitri, Melliana; Harahap, Indra; Ekowati, Endang (MASALIQ, 2023)
The main problem in this study discusses "Islamic Views Against Islamophobia" divided into two sub-problems, namely: 1) What is meant by Islamophobia; 2) What is the attitude of Islam towards Islamophobia. This study aims to look at Islamophobia, Islamic attitudes towards Islamophobia, and provide views of students of the Study of Religions regarding Islamic views on Islamophobia. In this research, a descriptive approach is used to provide accurate and factual descriptions and descriptions of properties, facts, relationships, views, activities, attitudes, processes, and how phenomena can impact them. Library research collects data and information from the library to be used as a basis for research. In addition, this research was conducted through a historical approach; the aim of this approach is to trace how certain ideas arose and developed over a period of time. The findings obtained from this study are that in the Islamic view, Islamophobia occurs through immoral acts by caring for Muslims. Even though Islam itself forbids mutual respect for all religions and beliefs, so there is no place for hate or hatred towards Muslims. Islam also emphasizes the importance of calm, safety and prosperity among human beings, regardless of religion, race or culture. The results of this study are that Islamophobia occurs because of a bad attitude towards Islam, the culprit could be through people who are non-Muslims and people who are Muslims themselves. Views about Islam which are considered to tend to be oppressive and tend to be violent in spreading terror. Therefore, views about Islam can be conveyed more optimally through various available facilities such as through the mass media. Efforts to introduce beauty, values of tolerance, love, brotherhood and Islamic compatibility with today's developments have become easier to do.